2015
DOI: 10.1177/0255761415620530
|View full text |Cite
|
Sign up to set email alerts
|

Levels of music performance anxiety and test anxiety of Turkish prospective music teachers in piano exams

Abstract: The purpose of this study was to determine the anxiety of prospective music teachers (N = 129) during piano exams and to examine the effects of peer and self-assessments on anxiety and exam achievement of individuals with high performance and test anxiety (n = 5). Female students were more anxious compared to males, students of the fourth class were the most anxious, and students who had graduated from fine arts high schools had lower anxiety levels. There was a positive and significant relation between test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
(47 reference statements)
2
12
0
1
Order By: Relevance
“…Piano players who want to improve their psychological quality must first improve their ability to adjust themselves. The psychological control skills required for performance are actually cultivated during the practice (Guven, 2017). The specific psychological control methods are shown in Table 4.…”
Section: Students' Psychological Control In the Process Of Piano Performancementioning
confidence: 99%
“…Piano players who want to improve their psychological quality must first improve their ability to adjust themselves. The psychological control skills required for performance are actually cultivated during the practice (Guven, 2017). The specific psychological control methods are shown in Table 4.…”
Section: Students' Psychological Control In the Process Of Piano Performancementioning
confidence: 99%
“…MPA’s impact on musicians has a pronounced sex bias, with females reporting being affected more frequently by MPA symptoms than males at various stages of their careers. Research has now shown that young girls learning music (Ryan, 2004), teenage girls (Patson, 2014), higher education female students (Guven, 2017; Struder et al, 2011) and even professional female players (Kenny, Driscoll, & Ackermann, 2014) are reporting a higher incidence of MPA symptoms than their male peers. Music educators need to be aware of the higher incidence of MPA in females when helping their students to manage its affects.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, MPA is associated with anxiety suffered before, during and after musical performance, either as a soloist or as a member of a group, regardless of the type of musical instrument (Barbar, Crippa, & Osorio, 2014a; Brodsky, 1996; Gerling & Dos Santos, 2015; Papageorgi, Hallam, & Welch, 2007; Ryan & Andrews, 2009). As in other anxiety disorders, it manifests itself at a cognitive, motor and physiological level (Herrera, Jorge & Lorenzo, 2015); the repercussions on the physiological level are particularly significant, since they can directly affect the quality of a musical interpretation (Guven, 2015; Studer, Danusera, Hildebrandt, Arial, & Gomez, 2011). These components are not highly connected with one another in musicians who display low levels of performance anxiety, but they are highly interrelated in other cases.…”
Section: Introductionmentioning
confidence: 99%